EVALUATION OF SPECIAL AUTONOMY IN IMPROVING COMMUNITY WELFARE IN ACEH PROVINCE - Rasaili, Wildan; Andika, Fajri; Ilyasi, Ilyasi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
This research focuses on the evaluation of Aceh Province's special autonomy and public welfare, using several approaches; special autonomy, public policy, public policy evaluation, and public welfare. This research uses qualitative research methods through library research, so the research data used is data sourced from books, journals, and government reports, as well as other literature related to the research topic. The results show that the implementation of special autonomy in Aceh is still far from expectations, especially in improving people's welfare. In the health sector, during the 2016-2020 period, life expectancy increased from 69.51 to 69.93. Meanwhile, in the field of education, the population that has completed tertiary education (DI/II/III, DIV / S1, professional and S2 / S3) experiences a fairly high imbalance between urban and rural areas, namely 17.08 percent in urban areas and only 8.54 percent in rural areas. Meanwhile, in the economic field, Aceh is among the five poorest provinces in Indonesia. The number of poor people in Aceh in September 2021 was 850,260 people.